Social networks in determining migration and labour market outcomes: evidence from the German reunification - Helmut Rainer; Thomas Siedler (University of Essex, Institute for Social and Economic Research (ISER), 2008)
This paper empirically examines social network explanations for migration decisions in the context of the German reunification. Using longitudinal data from the German Socio- Economic Panel, we first show that the presence of family and friends in West Germany is an important predictor for the migration hazard rate of East Germans. We then explore whether pre-migration networks have a discernible impact on the economic and social assimilation of East German immigrants in West Germany. We find that East German immigrants are more likely to be employed, and to hold higher-paying jobs, when socially connected to the West prior to emigrating. East Germans immigrants with pre-migration networks also appear to be more integrated into their Western host communities than movers without preexisting social ties.
Keywords: 330